Treatment Resistant Severe Digital Ischemia Associated with Antiphospholipid Syndrome in a Male Patient with Systemic Sclerosis - Orhan Küçükşahin; Aşkın Ateş; Alexis K. Okoh; Emre Kulahcioglu; Murat Turgay; Gülay Kınıklı (Case Reports in Rheumatology)
We report the case of a male patient with limited cutaneous systemic sclerosis (SSc) that was complicated with severe digital ischemia, resistant to medical treatment. Due to the lack of treatment response, further laboratory and imaging studies were conducted. Findings were compatible with antiphospholipid syndrome and oral warfarin was added to the treatment regimen. After successful anticoagulation no further recurrences of digital ischemia were seen. An underlying etiology in SSc patients with treatment resistant digital ischemic necrosis should be suspected for accompanying antiphospholipid syndrome (APS).